Clinical significance and long-term prognosis of ulcerative colitis patients with appendiceal orifice inflammation - Kyong Wook Kuk; Ji Yeon Gwon; Jae Seung Soh; Hyun Lim; Ho Suk Kang; Sung-Hoon Moon; Abebe Muraga; Ji Won Yoo (BMC Gastroenterology, 2022)
Abstract Background Appendiceal orifice inflammation (AOI) or peri-appendiceal red patch is a skip lesion with segments of continuous colitis from the rectum. Frequently observed in ulcerative colitis (UC) patients, this lesion might be associated with proximal extension in some studies. However, the clinical significance of this lesion and long-term outcomes including therapy remain unclear. Thus, the aim of this study was to evaluate the clinical implication of AOI during long-term periods in patients with UC. Methods We retrospectively reviewed 376 patients with UC who performed complete colonoscopic examinations between April 2000 and December 2020. We compared clinical characteristics and outcomes of patients manifesting AOI with those who did not show AOI during a mean follow-up period of 66.1 months. Long-term outcomes included maximal extent of colitis, proximal extension, therapeutic medical histories, UC-related hospitalization, and relapse. Results Ninety-eight (26.1%) patients showed AOI without evidence of inflammation in the right colon. Mild disease activity at the diagnosis of UC was more included in patients with AOI than in those without AOI. Other baseline characteristics including disease extent, smoking history, external intestinal manifestation, and terminal ileal ulceration were not significantly different between the two groups. During follow-up periods, patients with and without AOI showed no significant difference in proximal extension, Mayo endoscopic score at the last endoscopic examination, UC-related hospitalization, or relapse. Of medication history, patients with AOI were less included in the group treated with high-dose aminosalicylates than those without AOI. However, therapeutic histories of steroids, immunosuppressive agents, and biologics were not significantly different. Of 62 patients with AOI who underwent follow-up colonoscopy, 36 (58.1%) showed resolution of AOI. Clinical outcomes of the resolution group were not different than those of the non-resolution group. Biopsy results of 77 patients with AOI showed chronic active or erosive colitis. Conclusions Long-term outcomes of UC patients with AOI were not different from those without AOI. Outcomes of resolution and non-resolution groups of AOI patients were not different either. Thus, AOI might have no prognostic implication in distal UC patients.